DESAIN STRUKTUR GEDUNG 24 LANTAI DENGAN SISTEM RANGKA PEMIKUL MOMEN KHUSUS (SRPMK) DAN SISTEM GANDA MENGGUNAKAN PERFOMANCE BASED DESIGN BERDASARKAN SNI 2847:2019 - Andika Hadi Pranata; Tony Hartono Bagio; Julistyana Tistogondo (Fakultas Teknik, Universitas Wiraraja, 2021)
A reinforced concrete building concrete reinforced that floored many extreme vulnerable to collapse if it is not well planned. Therefore, needed a planning structure that can qualify the criteria of strenght, serviceability, safety, and durability. The performance of a building will work and be more optimal if structural planning and analytical methods are correct. This planning is aided by a 17th version of ETABS program, the process of planning is made based on structural concrete requirements for buildings (SNI 2847-2019) and earthquake resistance planning ordinances (SNI 1726-2019). The purpose of this building structure planning is to produce calculations based on SNI. This design produces a main beam with type 35/70 with 2D22 top & bottom 2D22 reinforcement and D10-125 & D10-300 stirrup reinforcement, the second type 50/100 with 4D22 top & bottom 2D22 reinforcement and D10-125 & D10-300 stirrup reinforcement. Sec-beam type 25/50 with 2D16 bottom & 2D16 top reinforcement and D10-125 & D10-225 stirrup reinforcement. One way plate 14cm thick with D10-200 reinforcement. Column type 145x145 with 28D22 reinforcement & D10-125 stirrups, 135x135 type with 24D32 reinforcement & D10-125 stirrups, 110x110 type with 16D32 reinforcement & D10-125 stirrups, 100x100 type with 12D32 reinforcement & D10-125 stirrups. and 1 type of shearwall with a wall thickness of 40cm with 2D13-100 boundary reinforcement & 2x5D16-150 Ties.